U.S. Corporate Income Taxation and the Dividend Remittance Policy of Multinational Corporations - Ness, Walter L. (Journal of International Business Studies, 1975)
Features of the U.S. taxation of the income of multinational corporations are shown to affect the minimum rate of return required on the unremitted profits of foreign subsidiaries. The article develops criteria that should be used by the firm as the minimum required return on reinvested earnings as the result of fiscal devices such as tax deferral, the foreign tax credit, and the special tax treatment of subsidiaries in less developed countries.